Pengaruh Literasi Keuangan, Gaya Hidup Hedonis, dan Self-Control Terhadap Perilaku Konsumtif Pengguna Shopee Paylater - Amaliya Fitriyana; Amalia Nur Chasanah; Pradana Jati Kusuma; Almira Santi Samasta (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine financial analysis, hedonic lifestyle, and self-control on the consumer behavior of Shopee Paylater users. The rapid development of e-commerce in Indonesia has also increased BNPL services, especially the Shopee Paylater platform, among Generation Z in Semarang City. The study used an associative quantitative approach implementing purposive sampling and online data presentation, and the data was processed using Smart PLS 3, with analysis using SEM-PLS techniques. The results showed that financial literacy and self-control had a negative and significant effect on consumer behavior, while a hedonic lifestyle had a positive and significant effect. The results prove that optimizing financial literacy and self-control skills play a significant role in reducing consumer behavior among Paylater service users.